Finding of some vectors of Chagas Disease in the department of Amazonas, Colombia, and its public health implications - GUALDRÓN, LUIS EDUARDO; BROCHERO, HELENA LUISA; ARÉVALO, CARLOS; PÉREZ, LIGIA DEL PILAR; SUÁREZ, MARTHA CECILIA; OLANO, VÍCTOR ALBERTO (Revista Colombiana de Entomología, 2001)
Triatomine insects from the localities of El Calderón (municipality of Leticia), Puerto Arica, Tipisca (municipality of Puerto Nariño), Puerto Curare and Puerto Córdoba (village of La Pedrera) in the Colombian department of Amazonas, were identified as Panstrongylus geniculatus and Rhodnius pictipes (Hemiptera: Reduviidae). This is the first report of insect vectors of Chagas' disease for the department. These species were found both inside human dwellings of settlers residing in the area. attracted by the light of traps for collecting insects or by dissection of natural ecotopes such as palm trees in localities where specimens had been previously detected, or where people were found to be infected by a positive serology test and/or where a case of acute Chagas' disease in a girl was confirmed in Puerto Curare in 1998. Rhodnius pictipes were found to be infected both with Trypanosoma cruzi and T. rangeli in palm trees located within the surroundings of human dwellings of settlers living in the area. The kind of human dwelling, the economic activity of its residents, and the geographic conditions of the area, amongst other factors, increase the probability of man vector contact further increasing the risk of transmission of the parasite. More detailed studies of the biology and distribution of triatomine insects in the department of Amazonas are necessary which, together with epidemiological studies, will help establish the real situation of this disease in the region and identify possible control strategies in order to avoid new acute cases and control emerging endemic foci of Chagas' disease in the Colombian Amazon region. Recommendations are included for the entomological and epidemiological surveillance of Chagas' disease in the department of Amazonas.